2020
DOI: 10.21203/rs.3.rs-59388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated Ambulatory Blood Pressure Measurements Are Associated With a Progressive Form of Fabry Disease

Abstract: Background and objectivesPublished data on hypertension incidence and management in Anderson-Fabry disease are scanty and it remains to be shown how much an elevated blood pressure contributes to the patient’s organ damage. Therefore, we have assessed blood pressure values and their correlations with clinical findings in a cohort of Fabry patients.MethodsBetween January 2015 and May 2019, all adult Fabry patients (n = 32; n = 24 females, n = 8 males) referred to our institute were enrolled. Data regarding hype… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…They concluded that a decrease in heart rate variability, rather than an increase in blood pressure variability, might be an early indicator of FD (22). Another study conducted by Rossi et al also demonstrated a lower prevalence of hypertension in patients with ESKD, pre-renal, and patients with transplants (23). In our study, there was a signi cance (p = < 0.001) between hypertension and patients with alpha-Gal-A levels < 500pg/ml when the univariate analysis was employed.…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that a decrease in heart rate variability, rather than an increase in blood pressure variability, might be an early indicator of FD (22). Another study conducted by Rossi et al also demonstrated a lower prevalence of hypertension in patients with ESKD, pre-renal, and patients with transplants (23). In our study, there was a signi cance (p = < 0.001) between hypertension and patients with alpha-Gal-A levels < 500pg/ml when the univariate analysis was employed.…”
Section: Discussionmentioning
confidence: 96%
“…Schiffman et al [26] conducted a study involving 279 male and 168 female FD patients and reported that nearly 80% of both males and females with CKD at baseline were hypertensive, while only about 50% of those with a baseline eGFR ≥60 mL/min/1.73 m 2 were hypertensive. In a recent study by Rossi et al [29], ambulatory monitoring showed elevated BP in 6 (18.75%) of 31 FD patients, and masked hypertension was present in 3 of them. The hypertensive patients had a lower GFR in comparison with normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%